CONSTRUCTION OF AUTHORITY IN CORPORATE CONTRACTS: TENSION BETWEEN FORMAL STRUCTURE AND PRACTICAL FLEXIBILITY IN THE PERSPECTIVE OF GENERAL LAW - Chandra, William; Lie, Gunardi (Journal of Multidisciplinary Issues, 2025)
Authority constitutes a fundamental legal basis in corporate business agreements. In practice, it is not uncommon to find contracts signed by individuals lacking full formal legal legitimacy, either because they fall outside the corporate authority structure or lack proper power of attorney or official appointment. This issue raises legal questions regarding the validity of agreements that are substantively agreed upon but defective in legal representation. This study aims to analyze the boundaries of authority in corporate agreements and to evaluate the general legal approach toward legal acts undertaken by unauthorized individuals. The method employed is a normative juridical approach with qualitative analysis of primary and secondary legal materials. The findings indicate that although positive law mandates formal authority, corporate practice often tolerates actions considered commercially valid, especially when there is implicit acceptance or good faith on the part of the involved parties. These findings suggest that the general legal approach needs to be reconstructed to address the challenges of modern contractual practices. This research contributes to corporate legal practice by emphasizing the need to strengthen internal verification mechanisms and recommending the development of adaptive legal norms, while also enriching theoretical discourse on the limits of authority in contract law.